Performance study of terahertz (THz) wireless systems for space applications - Wang, Boyi (Nanyang Technological University, 2022)
As one of the key technologies for 6G mobile communication, terahertz has abundant frequency band resources, capable of providing more than 20 GHz bandwidth and Tera bps communication rates. The channel characteristics draw a significant impact on the performance of wireless communication system. The transmission characteristics of terahertz waves in atmosphere are the basis of the space application of terahertz waves. The study of channel characteristics and modulation technology is of great importance for the application and development of terahertz waves. From the perspective of simulation, this dissertation firstly analyzes the atmospheric physical parameters, establishes a channel model for terahertz wave propagation in the space using atmospheric transmission theory, and simulates the effect of various weather conditions (clear, cloudy, rainy) on terahertz wave transmission. Following this, the Mie scattering theory is applied to calculate scattering intensity distributions and attenuation characteristics of terahertz waves in dust environments with specified size distributions. A thorough analysis of the modulation part of terahertz communication is provided, and the modulation performances of 16QAM and QPSK are compared.